ENTREPRENEURSHIP EDUCATION AS A DRIVER OF ENTERPRISE INNOVATION AND ECONOMIC DEVELOPMENT: A CASE STUDY OF UNESCO’S ENTREPRENEURSHIP EDUCATION NETWORK (EE-NET) - Subramaniam, Mehela; Mohd Salleh, Sri Sarah Maznah; Muhd Yusuf , Dayang Hasliza (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
Entrepreneurship education is widely recognised as a critical driver of enterprise innovation and sustainable economic development, particularly in developing and emerging economies. This study examines the role of entrepreneurship education in fostering firm-level innovation and supporting inclusive economic growth through a qualitative case analysis of the UNESCO Entrepreneurship Education Network. The research draws on secondary data from academic literature, policy documents, institutional reports, and publicly available databases produced by the United Nations Educational, Scientific and Cultural Organization. A document-based thematic analysis is employed to explore how entrepreneurship education initiatives influence innovation capacity, entrepreneurial ecosystems, and broader development outcomes. The findings indicate that entrepreneurship education significantly enhances individuals’ entrepreneurial competencies, enabling them to identify opportunities, develop innovative business models, and contribute to enterprise-level innovation. Beyond individual capability development, the study reveals that entrepreneurship education functions as an institutional mechanism that links educational systems, policy frameworks, and innovation ecosystems. In this context, the UNESCO Entrepreneurship Education Network demonstrates how coordinated regional and international collaboration can strengthen entrepreneurship education through inclusive policy frameworks, knowledge sharing, and capacity-building initiatives among governments, universities, and industry stakeholders. A key insight of the study is that network-based and institutionally supported entrepreneurship education initiatives can create enabling environments that stimulate innovation-driven entrepreneurship and support inclusive economic participation. The programme’s alignment with the Sustainable Development Goals further highlights the potential of entrepreneurship education to contribute to broader development priorities such as employment creation, social inclusion, and sustainable economic transformation. This research contributes to the entrepreneurship and innovation literature by providing empirical evidence on how international educational networks can reinforce institutional frameworks that support enterprise innovation and economic development. The findings underscore the importance for governments and higher education institutions to integrate entrepreneurship education into national innovation systems and development strategies to promote equitable and sustainable growth.